2014
DOI: 10.1007/s00270-014-0884-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Results After Directional Atherectomy of Calcified Stenotic Lesions of the Superficial Femoral Artery

Abstract: In this subgroup of patients with POD and calcified stenotic lesions, atherectomy was successfully applied to decrease the plaque burden. Results after 3 years showed a significant decrease of Rutherford score with persistent improvement of ABI and reasonable patency rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…It was not possible to determine if these findings were statistically significant due to the small number of cases. However, the percutaneous directional atherectomy has been shown to be a minimally invasive and safe interventional therapy that achieves a high patency rate and requires a low use of stents (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…It was not possible to determine if these findings were statistically significant due to the small number of cases. However, the percutaneous directional atherectomy has been shown to be a minimally invasive and safe interventional therapy that achieves a high patency rate and requires a low use of stents (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…This technology can also be used for other stenotic conditions such as the femoral artery especially for superficial targets. Currently, this condition is under clinical evaluation using other technologies such directional atherectomy [37].…”
Section: Discussionmentioning
confidence: 99%
“…20 When distal arterial embolization occurs, suction the plaque or dilate the balloon to promote plaque adherence and restore the lumen diameter. Minko et al 21 studied 53 patients with superficial calcification stenosis (total of 59 lesions) treated with the Hawk system and reported that 7 (1.19%) had distal arterial embolization during surgery which were successfully removed by catheter suction. In our study, we used the same method during surgery and successfully removed the embolization caused by plaque shedding.…”
Section: Safety and Efficacy Of The Turbohawk Plaque Excision Systemmentioning
confidence: 99%